2017
DOI: 10.17509/ijal.v7i1.6868
|View full text |Cite
|
Sign up to set email alerts
|

Pragmatic and Rhetorical Strategies in the English-Written Jokes

Abstract: Understanding verbal jokes in English is problematic for English as Foreign Language (EFL) readers since understanding the jokes requires understanding their linguistic, cultural and social elements. Since a joke constitutes a complex and paradoxical phenomenon, it needs multiple approaches of analyses-such as pragmatic and rhetorical analyses-in order to investigate the multiple layers of meanings it carries. Recently there has been a shift in humor studies, emphasizing linguistic humors and involving the fie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 19 publications
1
7
0
3
Order By: Relevance
“…We specifically studied whether the "setup and punchline" (Rochmawati, 2017) approach is used in funny headline generation, where the humor comes toward the end of the joke after a setup at the beginning. This has been verified numerically for funny cartoon captions by Shahaf et al (2015).…”
Section: Setup and Punchlinementioning
confidence: 99%
“…We specifically studied whether the "setup and punchline" (Rochmawati, 2017) approach is used in funny headline generation, where the humor comes toward the end of the joke after a setup at the beginning. This has been verified numerically for funny cartoon captions by Shahaf et al (2015).…”
Section: Setup and Punchlinementioning
confidence: 99%
“…Hossain et al ( 2019) also found evidence that the funniest headlines had their replacement word often positioned towards the end of the headline. This finding corresponds to the "setup and punchline" approach (Rochmawati, 2017): while a joke or headline builds up towards a certain expectation, the ending is suddenly changed to something unexpected that is still coherent, thus producing a humorous effect. In light of these findings, we also added the position of the edited word in the sentence as a feature.…”
Section: Feature Engineeringmentioning
confidence: 64%
“…Other expert, Wijana (2017), observes representations of humor in funny story books. Rochmawati (2017) took different are related humor which deals with humor in English texts. The realization of humor in cartoons using the theory of semantic presupposition was done by Dewi (2008).…”
Section: The Backgroundmentioning
confidence: 99%